Mad men unzipped : fans on sex, love, and the sixties on TV - Dill-Shackleford, Karen, 1969-; Vinney, Cynthia, 1978-; Hogg, Jerri Lynn; Hopper-Losenicky, Kristin, 1984- (University of Iowa Press, 2015)
"Four media psychologists who also just happen to be dedicated Mad men fans explore how the show's viewers make meaning from fictional drama. The authors also interviewed several contemporary advertising industry professionals, getting their inside view of the business in its modern guise and what they make of the show's vision of their past. The result is ... psychological research that crunches and codes online fan commentary to understand the ways that people use the show to debate complex social issues, from sex and alcohol to gender roles, parenting, and advertising itself"--Amazon.com